NATURAL GROUNDS OF HISTORICAL PROCESSES - Turdiboev Bozor Khudoyberdievich (European Journal of Interdisciplinary Research and Development, 2023)
Philosophical analyzes of historical processes and natural factors that cause occurrence of events are presented in this article. Also, the natural foundations and geographical factors of the emergence of civilizations were studied.